Comment initier en mathématiques la production d’une notation et ses usages à partir de l’activité des élèves ? - Serge Quilio; Dominique Forest (Recherches en Éducation)
We seek to describe verbal and non verbal interactions and how a teacher teaches mathematics in a learning situation where the production of mathematical concepts and a marking-system is developed from the pupils’ activity with the teacher’s guidance. We will describe the initial stages of teaching fractions to 10 year-old pupils from primary school, and more specifically the pupils’ elaboration of a means to designate sizes much smaller than single units, such as the thickness of a sheet of paper (much less than a millimeter, requiring a slide rule for measurement), the mass of a nail (well below the level of sensitivity on the Roberval balance), or the capacity of a thimble etc. We show how a teacher together with the pupils, manages to develop common reference points, objectives and rules, in other words a shared learning-environement.